SYNTHESIS, CHARACTERIZATION AND BIOLOGICAL EVALUATION OF 3-FORMYL INDOLE BASED SCHIFF BASES - Gurvinder, Singh; Prabhsimran, Singh; R. K., Dhawan (Journal of Biomedical and Pharmaceutical Research, 2018)
In order to develop new antimicrobial agents, a series of 3-formyl indole based Schiff bases were synthesized by reacting 3-formyl indole(indole-3-carboxaldehyde) with substituted aniline taking ethanol as solvent. The reaction was carried in the presence of small amount of p-toluene sulphonic acid as catalyst.All the synthesized compounds were characterized by IR, 1H-NMR spectral analysis. All the synthesized compounds were evaluated for antimicrobial activity against two gram positive bacterial strains (B. subtilisand S. aureus) and two gram negative bacterial strains (P. aeruginosaand E. coli) and one fungal strain (C. albicans). All the synthesized compounds were found to have moderate to good antimicrobial activity. The  standard drug amoxicillin, fluconazole were used for antimicrobial activity. Among the synthesized compounds, the maximum antimicrobial activity was shown by compounds GS04, GS07, GS08 and GS10.